2009
DOI: 10.1111/j.1439-0523.2009.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

The extent and prevailing shape of spatial relationships in Polish variety testing trials on wheat

Abstract: Independence of observations is one of the basic assumptions of the analysis of variance. Performed randomizations prevent results from being biased in cases when independence is violated. The objective of the present paper is to find out the predominant shape of spatial relationships in Polish wheat variety testing trials. One of the possibilities is to apply some geo-statistical method (Cressie Noel 1993, Grondona andCressie 1991). Such an approach is used in this paper. Using the results of nearly 200 tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The model selections tend toward similar decisions insofar as the basic or random‐walk model is better suited to the small designs and nonlinear spatial models are better suited to the larger designs. There are other experimental situations in which the linear model ( r ) is also appropriate for experiments with higher treatment numbers, however, as Pilarczyk (2007) and Müller et al (2010) have reported. The idea that a particular covariance model is better suited than another for all subareas of the field or for a specific crop has been proven to be untenable.…”
Section: Discussionmentioning
confidence: 99%
“…The model selections tend toward similar decisions insofar as the basic or random‐walk model is better suited to the small designs and nonlinear spatial models are better suited to the larger designs. There are other experimental situations in which the linear model ( r ) is also appropriate for experiments with higher treatment numbers, however, as Pilarczyk (2007) and Müller et al (2010) have reported. The idea that a particular covariance model is better suited than another for all subareas of the field or for a specific crop has been proven to be untenable.…”
Section: Discussionmentioning
confidence: 99%
“…Each field experiment was conducted according to a two‐factor strip‐plot design with two replicates. The cultivars were randomly arranged in sub‐blocks (rows) and the two crop managements in perpendicular sub‐blocks (columns) (Pilarczyk, 2009). The area of a plot was 15 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The FA structure uses multiplicative terms for approximation of the unstructured variance-covariance matrix (Piepho, 1997;So and Edwards, 2009;Beeck et al, 2010;Cullis et al, 2010). In many previous studies, FA structures were recommended to model cultivar two crop managements in perpendicular sub-blocks (columns) (Pilarczyk, 2009). The area of a plot was 15 m 2 .…”
Section: Multienvironment Trialmentioning
confidence: 99%
“…For testing the global null hypothesis that all t treatments have equal mean, L′ will have t-1 linearly independent rows with pairwise contrasts. In general, the following problems occur with these tests (Kenward & Roger 1997, 2009Schabenberger & Pierce 2002):…”
Section: Introductionmentioning
confidence: 99%
“…For example, in split-plot and strip-plot designs, where treatment contrasts involve several variance components, it may be necessary to approximate the error degrees of freedom, particularly when missing data occur (Fai & Cornelius 1996;Spilke et al 2005). Studies by Kenward & Roger (1997, 2009, Gomez et al (2005) and Schaalje et al (2002) demonstrate that the validity of tests depends on the method chosen, the underlying covariance model and its parameter values, the parameterization of the model and the sample size. When using a spatial add-on component in the analysis of field trials, however, the data structures are not directly comparable, so that results of these studies do not apply.…”
Section: Introductionmentioning
confidence: 99%